QoS Support with Taguchi Method in Simulation Modelling Hybrid Architecture of Optical and Multi-Hop Wireless Ad Hoc Networks - Wong, M. A.; Elias, Shamsul Jamel; Idrus, Sevia Mahdaliza; Zulkifli, Nadiatulhuda; Iqbal, F. (International Journal of Engineering and Technology, 2026)
Majority of the resource consumption is consumed for their operation in the access network of mobile wireless part because of its dynamic topology and limited wireless transmission range of each mobile user's. This article presents a technique using OMNeT++ software for building a design of experiment simulation model with Taguchi optimization method based on mobile ad hoc network (MANET) of AODVUU communication protocol to in cooperate with multiple layers framework. This particular framework is for deployment over future passive optical network (PON) known as the efficient routing Last Mile Mobile Hybrid optical wireless access network (erLMMHOWAN). It is for performing effective network quality of service evaluation that consider a number of nodes over which the MANET may operate. Its performance is examined on the identified performance metrics like the network capacity and energy consumption. Simulation result shows for the random mobile connectivity in this convergence of heterogeneous optical wireless network can have better performance based on optimized front-end of access network using wireless ad hoc routing.